(untitled) (Journal of Plant Disease Sciences, 2024)
Green gram (Vigna radiata) belongs to the family Leguminaceae and originated from the Indian subcontinent where it was domesticated as early as 1500 BC. Cultivated mungbean was introduced to southern and eastern Asia, Africa, Austronesia, the Americas and the West Indies. Green gram is excellent source of high quality protien. Green gram is consumed as whole grains, sprouted from as well as daal in a variety of ways in homes. It is also used as green manuring crop. Mungbean can be used as a feed.